The influence of heterogeneity on coastal groundwater flow - physical and numerical modeling of fringing reefs, dykes and structured conductivity fields. (March 2018) - Houben, Georg J.; Stoeckl, Leonard; Mariner, Katrina E.; Choudhury, Anis S.
Highlights : Heterogeneity strongly influences coastal groundwater flow. Physical and numerical models were done for discrete (Dykes, fringing reef) and spatially distributed heterogeneity. Dykes lead to compartmentalization of aquifer and preserve saline water on the landward side for longer periods of time. Fringing reefs lead to bimodal freshwater flow to the ocean, (a) at the beach face, (b) in submarine springs at the reef bottom. This play a major role for nutrient transport into coastal ecosystems. Bimodal flow confirmed by field data. For structured conductivity fields, longer aquifer compartments lead to a higher resulting hydraulic conductivity and a movement of the wedge toe further inland. Abstract: Geological heterogeneity of the subsurface, caused by both discrete features and spatially distributed hydraulic conductivity fields, affects the flow of coastal groundwater. It influences the shape and the position of the interface between saltwater and freshwater, as well as the location and flux rate of freshwater discharge to the ocean. Fringing reefs lead to a bimodal regime of freshwater discharge, with discharge at the beach face and through deeper, submarine springs. Impermeable vertical flow barriers (dykes) lead to an impoundment of fresh groundwater and a compartmentalization of the aquifer but also to a delayed expulsion of saline water. Spatially distributed conductivity fields affect the shape of the interface and the geometry of the saltwater wedge. Higher effective conductivities lead to a further landward intrusion of the wedge toe. These flow characteristics can be important for groundwater extraction, the delineation of protection zones and the assessment of contaminant transport to coastal ecosystems.